An EIoT system designed for ecological and environmental management of the Xianghe Segment of China's Grand Canal. Issue 4 (3rd July 2016) - Zheng, Rubin; Zhang, Tianhai; Liu, Zhifang; Wang, Haowei
ABSTRACT: Ecological and environmental protection of the Xianghe Segment of China's Grand Canal (XSCGC) has gained increasing attention. The Xianghe Segment is located in a highly urbanized area, and it is imperative to promote the environmental quality of this region. Application of the Environmental Internet of Things (EIoT) can greatly improve the performance and effectiveness of ecological and environmental management. In this study, we propose and describe an ecological and environmental management system based on EIoT to monitor canal construction. This system includes a digital management platform and an environmental early warning platform, which monitor and manage water resources, soil–plant biodiversity, waste production, and energy use in real time. Based on a regional analysis of the construction plan and environmental and anthropogenic factors, the key monitoring areas were determined and the spatial distribution of the EIoT sensing layer was arranged. The construction of EIoT should be carried out in three stages to effectively monitor the ecology and environment of the study region. The application of landsenses ecology to the EIoT system will help improve ecological planning.